EVALUASI USABILITY MICROSOFT TEAMS MENGGUNAKAN SYSTEM USABILITY SCALE DI STMIK MIKROSKIL MEDAN - Raissa Amanda Putri; Salsalina Br Sembiring (Jurnal Informatika Kaputama (JIK), 2021)
The COVID-19 pandemic requires teaching and learning activities that were previously carried out face-to-face to be implemented in the form of Distance Learning. This causes the use of eLearning in STMIK Mikroskil to increase rapidly, so STMIK Mikroskil decided to start implementing a collaborative software, namely Microsoft Teams. In using Microsoft Teams, some students are still confused about using the Microsoft Teams application. Usability evaluation of Microsoft Teams using the System Usability Scale (SUS) is done as a first step to assess the success of implementing Microsoft Teams. Based on the results of the SUS questionnaire, it was obtained a score of 72 with a “Good” rating and a letter grade “B”.